Mechanical Vector Control of Periplaneta Americana with Baiting Gel Application Containing Borax and Sulfur Material - Mela Firdaust; Bayu Chondro Purnomo (JURNAL KESEHATAN LINGKUNGAN, 2019)
Periplaneta Americana has long been acknowledged as mechanical vector for infectious diseases. Baiting gel is considered as an advantegous mechanical vector control because it is relatively affordable and convenient for users. However, further studies to understand dose-response effects and effective ingredient composition still limited. Therefore, the aim of this research was to analyze the effect of the combination doses of baiting gel with active ingredients boric acid and sulfur materials on Periplaneta americana mortality. This research was true experimental with Randomized Controlled Trial (RCT) study design. The researchers intervened the formula of baiting gel with a combination of boric acid and sulfur at different doses. The treatment of baiting gel at various dose levels produced a significant difference in the mortality of Periplaneta americana imago. Partial eta squared values showed the model design formed and the dose of baiting gel that had been applied had an effect on the mortality of Periplaneta americana imago at 90.4%. The observed power results show that the percentage to reject the hypothesis H0 for all diversity is 100%. The most effective dose in killing Periplaneta Americana cockroaches is a combination of Boric Acid: 10 grams and Sulfur: 0.25 grams. The conclusion of this research was to it is recommended to determine the weight of baiting gel before and after the application in order to optimize the results.